Selective media in the isolation of tubercle bacilli from tissues - Mitchison, D. A. (1973)
Direct culture on Lowenstein-Jensen slopes and on three media made selective for tubercle bacilli by the addition of four antibacterial agents was compared with guinea-pig inoculation on 490 tissue specimens. Tubercle bacilli were obtained from 15 specimens by culture and 14 by guinea-pig inoculation; only one specimen was positive by guinea-pig and not by culture. The most efficient culture medium was a selective 7H11 slope. Routine guinea-pig inoculation has been replaced by a wider range of culture procedures.